Letter - Joint Strike Committee, NUR, Lancaster Branch, 10 May 1926 (Lancaster)
1926-05-10 "Letter - Joint Strike Committee, NUR, Lancaster Branch, 10 May 1926" [g0066001.jpg], 10 May 1926, Joint Strike Committee, NUR, Lancaster Local Organisation